The Optimization and Analysis of Hydrocarbon Recovery under Injection of Biopolymer, Synthetic Polymer and Gels in a Heterogeneous Reservoir - Dike Fitriansyah Putra; Cenk Temizel (Journal of Earth Energy Engineering, 2018)
Water injection is a conventional method which increases the recovery by providing pressure support and displacing oil in the heterogeneous porous medium. Mobility ratio is important for a more efficient oil displacement by the injected fluid. Mobility ratio can be reduced using the fluids involving gelling agents. While polymers degrade and break up on experiencing sudden shear stresses and high temperatures, polymer macromolecules are forced to flow into narrow channels and pores where molecular scission processes can take place. It is importance to have a strong understanding of the use of the right type and amount of viscosity as a reduction agent. For polymer injection, a comparison of xanthan polymer and synthetic polymer mechanisms was conducted. A commercial full-physics reservoir simulator was coupled with a robust optimization and uncertainty tool to run the model, where a simplified gel kinetics was assumed to form a microgel with no redox catalyst. Control and uncertainty variables were set to investigate the sensitivity of this process using the coupled optimization and uncertainty tool. Results demonstrate deep penetration of gel and blocking of the high permeability bottom layers. Sensitivity studies indicate the relative merits of biopolymer, xanthan polymer in terms of viscosity effects vs synthetic PAM in terms of resistance factor vs in-situ gelation treatments and their crossflow dependence. Adsorption and retention of polymer and gel are permeability dependent. Considering the potential for application of gel solutions in the U.S. and throughout the world, this study illustrates the relative advantages of different treatments in terms of viscosity reduction in the same model in a comparative way, while outlining the significance of each control and uncertainty variable for better management of reservoirs where displacement efficiency is highly critical.